3D visualized tracing of rebar corrosion-inhibiting features in concrete with a novel chemical self-healing system. (20th April 2018) - Dong, Biqin; Ding, Weijian; Qin, Shaofeng; Fang, Guohao; Liu, Yuqing; Dong, Peng; Han, Shiwen; Xing, Feng; Hong, Shuxian
Highlights: A novel chemical self-healing system is designed for inhibiting rebar corrosion in NaCl solution. Rebar corrosion-inhibiting features are 3D visualized traced by X-ray computed microtomography(X-ray μCT) Rebar corrosion-inhibiting effectiveness with microcapsules is qualitatively analyzed from X-ray μCT results. Abstract: A novel chemical self-healing system, with sodium monofluorophosphate/ethyl cellulose microcapsules, is designed with the objective of inhibiting rebar corrosion in concrete materials under NaCl solution. The corrosive behavior is traced and analyzed in 3D visualization by the method of micro X-ray computed microtomography (X-ray μCT). Environmental scanning electron microscopy (ESEM) and texture element analysis microscopy (TEAM) are used to verify the results from the X-ray μCT measurement. The experimental results show that typical pitting corrosion features are detected directly by X-ray μCT. The chemical self-healing system, with sodium monofluorophosphate/ethyl cellulose microcapsules, can postpone the rust procedure and effectively inhibit the rust rate of rebar in a simulated corrosion environment. The corrosion-inhibiting performance becomes significant with the microcapsules increasing. Moreover, a linear relationship between volume losses of rebar and time is deduced from the X-ray μCT data. Corresponding corrosion ratios and corrosion rates are quantitatively calculated for comparison of the inhibition afforded by the chemical self-healing system.